THE STUDY OF HISTOTOPOGRAPHY OF GLYCOCONJUGATES IN THE PERSPECTIVE OF THE DEVELOPMENT OF LOCAL THERAPY OF STOMATOLOGICAL MAXILLARY SINUSITIS - Varzhapetyan, S.D.; Gulyuk, A.G. (World of Medicine and Biology, 2018)
Lectin can act as address agents, or vectors. The distribution of carbohydrate residues with high concentration in the regions of the mucous membrane of the maxillary sinus of 129 (100.0 %) patients, which were distributed according to etio-pathogenetic groups of stomatogenic maxillary sinusitis. The study showed that the saturation of N-acetylneuraminic acid dominates only in the basal cells of the Schneider membrane in the case of an odontogenic maxillary sinusitis. Sialyl(α2-6) galactose had high expression with traumatic form of iatrogenic maxillary sinusitis towards the other carbohydrate determinants, β-D-galactose was only in ciliary cells of patients with medical form of iatrogenic sinusitis. Most often, in Schneiderian membrane structures, L-fucose, and α-D-monozy had high expression of observed in all forms of dental maxillary sinusitis.
Keywords: lectinhistochemistry of the Schneiderian membrane; iatrogenic maxillary sinusitis; labeled medicines